Enhancing Early Childhood Literacy through Reading Corners: A Phenomenological Study at Thiflah Early Childhood Education, Aceh Besar - Rahimah, Rahimah; Mutmainnah, Mutmainnah; Rita, Cut Mirna; Wahyu Adibah, Khairiyyah Titi; Isdarianti, Novi Lidya; Fauzi, Indra (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This study explores the effectiveness of reading corners in enhancing literacy among early childhood learners at Thiflah Early Childhood Education (ECE) in Aceh Besar, Indonesia. Employing a phenomenological research design with qualitative methods, this study aims to understand the subjective experiences of educators and learners about literacy enhancement strategies. The research incorporated observations, interviews, and documentation, with a focus on the role of the reading corner in fostering literacy. Results indicated significant improvements in children’s engagement and comprehension in reading, writing, and arithmetic, attributed to the interactive and play-oriented learning environment. However, challenges such as insufficient resources and reliance on student teachers with limited experience were identified. The findings suggest that the reading corner approach, aligning with Indonesia's National Literacy Movement, can be a viable model for enhancing early literacy in various educational settings. The study recommends further research into the effectiveness of reading corners in diverse ECE contexts and emphasizes the need for resource enhancement and teaching methodology improvements. These insights are crucial for developing engaging, child-centric learning environments for early literacy development and overall child growth, contributing significantly to Indonesia's National Literacy Movement.